PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SENI BUDAYA BIDANG STUDI SENI RUPA MENGGUNAKAN MEDIA VISUAL SISWA KELAS VIII.1 SMP NEGERI 30 PADANG - SATRIO, Drs. Erfahmi,M.Sn, Drs. Abd. Hafiz,M.Pd (Serupa The Journal of Art Education, 2014)
The purpose of the research is to improve the activity and student learning outcomes. The research instrument is used is the observation sheets, and test results of students' learning. The successful achievement of specified is 75% of the number of students achieved mastery Minimum Criteria (KKM = 75). As for the increase in student activity, measured through assessment criteria specified. The results of the study to demonstrate the activity of students in the first cycle there is only one indicator that reached criterion lacking sufficient rest, and the second cycle there are two indicators that reached the best criteria. As for the learning outcomes of students in first cycle is gained an average of 73.91 and percentage of 71.87%, and the second cycle increased to 80.78 and percentage 90.63%.Key word: Increase, Activity, Results of Study, Students'